PROGRAM BIMBINGAN BELAJAR MATEMATIKA UNTUK ANAK-ANAK KURANG MAMPU DI LINGKUNGAN DESA HILISATARO - Welli Siswanti (Universitas Nias Raya, 2023)
The Mathematics Tutoring Program for underprivileged children in Hilisataro Village aims to enhance the understanding and mathematical skills of students from low-income families. In implementing this program, we identified the challenges faced by students in learning mathematics, including limited access to learning resources and inadequate teaching in schools. This program involves a series of tutoring activities designed with an interactive and enjoyable approach, utilizing active learning methods and simple teaching aids. We also engaged parents and the local community to support the children's learning process. The results of this program showed a significant improvement in students' understanding of basic mathematical concepts, as well as an increase in their motivation and self-confidence in learning. Additionally, the program successfully raised community awareness of the importance of mathematics education for children. Through consistent tutoring and holistic support, it is hoped that the children in Hilisataro Village can build a strong mathematical foundation, enabling them to continue their education more effectively in the future.This program is expected to serve as a model for similar initiatives in other villages facing comparable challenges.